How Can We Help People With Long-Term Health Conditions Understand and Engage in Physical Activity From Healthcare to Community Settings? Perspectives of Patients, Carers, and Professionals (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Physical activity (PA) is fundamental in managing long-term health conditions (LTCs), yet maintaining activity in day-to-day life remains a major public health challenge. Integrated pathways between primary care and community services are becoming sustainable solutions to support PA maintenance into community living for people with LTCs.We aimed to understand the needs and preferences of people with LTCs, their caregivers, and multi-sectoral professionals, regarding the development of an integrated pathway to maintain PA. This included barriers and facilitators to implementing a PA pathway for people with LTCs in the current United Kingdom context.Methods: We adopted a World Café approach to understand the needs of LTC public, healthcare professionals, and community professionals, and begin co-designing an integrated PA pathway in Southern England (UK). Four focus groups, involving people with LTCs (n = 21; aged 39–82 yrs.; July–August 2024), were complemented by 19 multi-sectoral professional (aged 26–66 yrs.; July–November 2024) and six carer interviews (aged 20–78 yrs.; November 2024–February 2025). Thematic analysis was used to interpret codes inductively without pre-defined domains, and the Capability, Opportunity, Motivation, Behaviour (COM-B) model used to frame the findings.Results: Pain, fatigue, and managing comorbidities limited LTC participants’ access to PA, whereas caregivers faced time and financial barriers. Primary care and community centres were deemed accessible and reliable locations to advertise local opportunities, but lacked current, LTC-appropriate activities. Local authority funding cuts limited professionals collaborating with other organisations. Community navigators (e.g. health coaches) were emerging as trusted ‘intermediaries’ between primary care and community services, to support PA maintenance as a public health approach. A centralised digital hub interlinking healthcare, health coaches, and community organisations was recommended to provide ongoing support for LTC public, via personalised and appropriate signposting/referral.Conclusion: Our findings highlight that PA pathways between primary care and community services should collaborate as a wider public health approach, to overcome financial constraints, share resources and expertise. Digital hubs involving health coaches can facilitate multi-sectoral partnerships and provide appropriate, ongoing support to maintain PA for LTC public into community life.Support/Funding Source: A Wessex Health Partners (June 2024–July 2025) Pilot Grant was supported by two UK NIHR undergraduate internships